A "Escola-sacrifício": representações dos alunos sobre a escola, o processo escolarização, a evasão escolar e a conciliação escola/trabalho. - Áurea de Carvalho Costa (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article was made from collected and analyzed data during a research wich we investigated the droppedout from eight grade night classes in the public schools of Rio Claro, from 1981 until 1991. We analyzed their representations about school, dropping-out, student's self-image and relationship between school and work, extracted from interviews with four dropped-out students. First, we did a statistic survey of enrolled and dropped-out students, number of opened and closed classes. We analyzed documents and interviewed a teacher's supervisor to apprehend the structured speech in the school about dropping-out and we concluded that dropping-out converts, to student's life, on stockade to insert at work with rights and to participate on constitution of public space in school.